The impact of role modeling on the professional identity of pre-service teachers - Flores Delgado, Lizette Drusila; Olave Moreno, Irlanda; Villarreal Ballesteros, Ana Cecilia (Universitas Pendidikan Indonesia, 2020)
Research shows that mentoring EFL pre-service teachers during the practicum element of teacher-training courses allow them to get experience and to develop, improve, and put into practice their teaching skills. This professional practice can impact the development of a positive or negative professional identity in teachers. Current literature, however, seems to focus on the shaping of teacher identity and learner identity, but there is little empirical research regarding the development and shaping of the identity of pre-service teachers. Pre-service teachers are the main actors of this practicum stage of teacher-training programs and, therefore, by working in collaboration and being supported by a mentor as a role model, they develop their professional identity. The present qualitative case study sought to explore the shaping and re-shaping of the professional identity of fifteen EFL pre-service teachers of a northern Mexican university and the impact of working with English teacher mentors as role models. Information gathered through the constant comparative method of data from the participants taken from their reflective journals, mentor-observations, and self-observations suggests that although working with a positive role model encourages the development of a stronger teacher identity and an improvement in their teaching practice, working with a bad role model can also have the same results.